Tenofovir alafenamide demonstrates broad cross-genotype activity against wild-type HBV clinical isolates and maintains susceptibility to drug-resistant HBV isolates in vitro - Liu, Yang; Miller, Michael D.; Kitrinos, Kathryn M. (Antiviral research, 2017)
Tenofovir alafenamide (TAF) is a novel prodrug of tenofovir (TFV). This study evaluated the antiviral activity of TAF against wild-type genotype A-H HBV clinical isolates as well as adefovir-resistant, lamivudine-resistant, and entecavir-resistant HBV isolates. Full length HBV genomes or the polymerase/reverse transcriptase (pol/RT) region from treatment-naïve patients infected with HBV genotypes A-H were amplified and cloned into an expression vector under the control of a CMV promoter. In addition, 11 drug resistant HBV constructs were created by site-directed mutagenesis of a full length genotype D construct. Activity of TAF was measured by transfection of each construct into HepG2 cells and assessment of HBV DNA levels following treatment across a range of TAF concentrations. TAF activity in vitro was similar against wild-type genotype A-H HBV clinical isolates. All lamivudine- and entecavir-resistant isolates and 4/5 adefovir-resistant isolates were found to be sensitive to inhibition by TAF in vitro as compared to the wild-type isolate. The adefovir-resistant isolate rtA181V + rtN236T exhibited low-level reduced susceptibility to TAF. TAF is similarly active in vitro against wild-type genotype A-H HBV clinical isolates. The TAF sensitivity results for all drug-resistant isolates are consistent with what has been observed with the parent drug TFV. The in vitro cell-based HBV phenotyping assay results support the use of TAF in treatment of HBV infected subjects with diverse HBV genotypes, in both treatment-naive and treatment-experienced HBV infected patients. •TAF in vitro antiviral activity was similar against wild-type genotype A-H HBV clinical isolates.•Drug-resistant HBV isolates were sensitive to TAF in vitro, as compared to the wild-type isolate.•Results support the use of TAF for treatment-naive and treatment-experienced HBV infected patients across genotypes.